Single-incision laparoscopic cholecystectomy reduced postoperative pain than three-incision laparoscopic cholecystectomy in patients with large gallstone, a retrospective study - Zhang, Zhiheng; Xu, Jiawei; Yu, Decai; Lin, Nacheng; Peng, Jin (Frontiers in Surgery, 2024)
AimTo compare the short-term outcomes between SILC and TILC depending on gallstone size.Material and methodsData from 114 patients with gallstones who underwent cholecystectomy hospitalized in Nanjing Drum Tower Hospital between June 2022 and October 2023 were collected. The gallstone diameter, the operation time, estimated blood loss, post-operative pain, complications post-operation, and length of hospital stay were all collected and examined.ResultsOf the 114 patients included in this study, 61 underwent SILC, and 53 underwent TILC. The pain score 6 h, 24 h post-operation was higher in the TILC group compared with the SILC group. Patients were divided into large (diameter > 2 cm) and small groups (diameter < 2 cm), larger gallstones significantly increased operation duration in the SILC group. For the TILC group, large gallstones significantly increased blood loss during the operation. The blood loss and pain scores were higher in the TILC group compared with the SILC group for patients with large gallstones.ConclusionIn this study, SILC and TILC both had comparable postoperative outcomes, while SILC significantly reduced postoperative pain than TILC. Moreover, SILC might be a suitable option for patients with larger gallstones (diameter > 2 cm) and helps reduce blood loss and postoperative pain.